(untitled) (World Bulletin of Education and Learning, 2025)
The Yunus Rajabiy Maqom Ensemble represents a cornerstone in the development and preservation of the classical maqom tradition in Uzbekistan. “As an institution devoted to the study and performance of national music, the ensemble serves as both a guardian of historical authenticity and a creative laboratory for artistic renewal” Rasulov, U. U. (2024).